2016
DOI: 10.5194/we-16-89-2016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of warming on a Mediterranean phytoplankton community

Abstract: Abstract. Predicting the responses of organisms is a complex challenge especially when water temperature is expected to increase over the coming decades, as a result of global warming. In this work the effects of warming on phytoplankton communities were investigated. An indoor experiment was performed, where water from a Mediterranean lagoon was incubated at different temperatures. Three treatments were applied in triplicate incubation units: the control (11 • C), 3 • C increase (14 • C), and 6 • C increase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 19 publications
(23 reference statements)
0
9
2
1
Order By: Relevance
“…Moreover, numerous studies have similarly reported a positive correlation between cyanobacteria abundance and temperature (Maugendre et al 2015;Chen and Laws 2017;Trombetta et al 2019), even during a fall bloom in the St. Lawrence Estuary (Bénard et al 2018). In addition, previous studies have reported higher abundances of pico-and nanophytoplankton under warmer temperatures (Pulina et al 2016;Trombetta et al 2019). In the present investigation, this trend was also observed for nanophytoplankton over the course of the experiment, but not for picoeukaryotes.…”
Section: Nanophytoplankton Cyanobacteria Bacteria and Virus Abundanmentioning
confidence: 88%
See 1 more Smart Citation
“…Moreover, numerous studies have similarly reported a positive correlation between cyanobacteria abundance and temperature (Maugendre et al 2015;Chen and Laws 2017;Trombetta et al 2019), even during a fall bloom in the St. Lawrence Estuary (Bénard et al 2018). In addition, previous studies have reported higher abundances of pico-and nanophytoplankton under warmer temperatures (Pulina et al 2016;Trombetta et al 2019). In the present investigation, this trend was also observed for nanophytoplankton over the course of the experiment, but not for picoeukaryotes.…”
Section: Nanophytoplankton Cyanobacteria Bacteria and Virus Abundanmentioning
confidence: 88%
“…For instance, an experimental increase in water temperature was reported to affect the relative abundance of phytoplankton, favouring small phytoplankton cells in the community, such as pico-and nanophytoplankton (Pulina et al 2016). Additionally, using in situ mesocosms, Vidussi et al (2011) reported a significant decrease in bacterial abundance, noting that trophic cascades led to this change.…”
Section: Introductionmentioning
confidence: 99%
“…Depth, transparency, temperature, salinity, dissolved oxygen (DO) and pH were directly measured in situ using portable equipment (Secchi disk, WTW multi 340i/SET, Wissenschaftlich-Technische Werkstätten, Dr-Karl-Slevogt-Straße 1, 82362, Weilheim, Germany). Discrete surface water samples were collected in 1 L polyethylene bottles and preserved at 4 • C for laboratory analysis of the following nutrients: NH 4 + -N, NO 2 − -N, NO 3 − -N, PO 4 −3 -P. Water samples for dissolved nutrients analyses were filtered using 0.45 µm pore size filters and immediately frozen (T = −20 • C) until analysis, while Chlorophyll-a (Chl-a; µg/L) extraction was conducted in 90% acetone for 24 h. All concentrations were measured according to American Public Health Association (APHA) [41]. For total phosphorus (TP), water samples were collected before filtering.…”
Section: Sampling Design Of Water Quality and Aquatic Macrophytesmentioning
confidence: 99%
“…Therefore, they represent an ecotone between marine, fresh-water, and terrestrial ecosystems showing some typical characteristics of all these types [1]. These characteristics often result in considerable seasonal changes of environmental variables (e.g., temperature, salinity) and large fluctuations in chemical parameters with consequences to many resident species [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Both global warming and eutrophication can mutually reinforce the symptoms and problems connected with them (Moss et al 2011). The abundance of relatively small-sized taxa, which also includes cyanobacteria, can increase significantly, while large-sized diatoms decrease because of climate warming (Pulina et al 2016). Consequently, cyanobacteria species become phytoplankton dominants, and since they are less edible for zooplankton, this can diminish energy flow to higher trophic levels (Elliott 2012).…”
Section: Introduction Phytoplankton Growth Patterns and Dominance Shiftsmentioning
confidence: 99%